Investigation of biaryl heterocycles as inhibitors of Wee1 kinase. Issue 12 (15th June 2019) - Mastracchio, Anthony; Lai, Chunqiu; Torrent, Maricel; Bromberg, Kenneth; Buchanan, Fritz G.; Ferguson, Debra; Bontcheva, Velitchka; Johnson, Eric F.; Lasko, Loren; Maag, David; Soni, Nirupama; Shoemaker, Alexander R.; et al.
Graphical abstract: Abstract: In continuation of our previous research towards the discovery of potent, selective and drug-like Wee1 inhibitors, 2 novel series of biaryl heterocycles were designed, synthesized and evaluated. The new biaryl cores were designed to enable structure−activity exploration of substituents at C-8 or N-8 which were used for tuning compound properties and to improve compound profiles. The lead molecule 33 demonstrated a desirable pharmacokinetic profile and potentiated the anti-proliferative activity of irinotecan in vivo when dosed orally in the human breast MX-1 xenograft model.